2016
DOI: 10.1007/s00484-016-1228-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison and appraisal of a comprehensive range of human thermal climate indices

Abstract: Numerous human thermal climate indices have been proposed. It is a manifestation of the perceived importance of the thermal environment within the scientific community and a desire to quantify it. Schemes used differ in approach according to the number of variables taken into account, the rationale employed, and the particular design for application. They also vary considerably in type and quality, method used to express output, as well as in several other aspects. In light of this, a three-stage project was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 107 publications
1
102
0
2
Order By: Relevance
“…Several complex thermal indexes were developed to date, describing and quantifying the thermal environment of humans and the energy fluxes between the human body and the surrounding environment. De Freitas and Grigorieva [79,80] carried out a three-stage study, providing a comprehensive register of 165 indexes suitable for the purpose, which were subsequently grouped and classified. Thus, they observed that indexes are almost designed for a specific application, so the choice depends on the context in which the index is used, as well as on the availability of the data needed to quantify it.…”
Section: Mathematical Models and Indexesmentioning
confidence: 99%
“…Several complex thermal indexes were developed to date, describing and quantifying the thermal environment of humans and the energy fluxes between the human body and the surrounding environment. De Freitas and Grigorieva [79,80] carried out a three-stage study, providing a comprehensive register of 165 indexes suitable for the purpose, which were subsequently grouped and classified. Thus, they observed that indexes are almost designed for a specific application, so the choice depends on the context in which the index is used, as well as on the availability of the data needed to quantify it.…”
Section: Mathematical Models and Indexesmentioning
confidence: 99%
“…Strong wind, on the other hand, can offset the heat stress by increasing the rate of perspiration and therefore increasing the loss of latent heat from the human body to its surrounding environment. Plus, the scientific community has proposed over 160 human thermal climate indices to provide a precise quantification of the thermal environment over past 100 years (de Freitas & Grigorieva, ; de Freitas & Grigorieva, ). Owing to the large number of thermal indices, considerable uncertainty resides in measuring the exact thermal environment because of parameter simplification and different combinations of variables.…”
Section: Assessment Of Climate Change Impacts On Human‐perceived Tempmentioning
confidence: 99%
“…These summarize the effects of the individual meteorological parameters on thermal comfort or stress into one quantity by using weighted equations or heat balance models [87]. In total, more than 165 thermal indices have been developed [88] with different characteristics and application areas [89,90].…”
Section: Human Comfortmentioning
confidence: 99%